Special integrals of Gradshteyn and Ryzhik, the proofs - Moll, Victor H. (Monographs and research notes in mathematics, 2015)
A Guide to the Evaluation of IntegralsSpecial Integrals of Gradshetyn and Ryzhik: The Proofs provides self-contained proofs of a variety of entries in the frequently used table of integrals by I.S. Gradshteyn and I.M. Ryzhik. The book gives the most elementary arguments possible and uses Mathematica® to verify the formulas. Readers discover the beauty, patterns, and unexpected connections behind the formulas. Volume I collects 15 papers from Revista Scientia covering logarithmic integrals, the gamma function, trigonometric integrals, the beta function, the digamma function, the incomplete beta